Next-generation sequencing guides diagnosis and treatment in a complex presentation of ALK-positive anaplastic large-cell lymphoma: a case report - Vaid, Tejasvini; Gunning, Thomas S.; Cohen, Rachel; Della Pia, Alexandra; Voss, Jason; Weber, Melinda; Pecora, Andrew L.; Leslie, Lori A.; Feldman, Tatyana; Goy, Andre H.; Albitar, Maher; Ip, Andrew (Frontiers in Oncology, 2025)
Next-generation sequencing (NGS) technology is being increasingly utilized in the management of cancer patients due to its diagnostic, therapeutic, and prognostic value, and potential to inform use of targeted therapy. We report a case wherein performing NGS testing proved to be a critical component in diagnosis and therapeutic decision making. The case was of a patient who presented with diffuse osteolytic bone lesions that on biopsy showed an undifferentiated malignancy. A diagnosis of poorly differentiated sarcoma was made at an outside institution and carboplatin and paclitaxel was initiated. However, NGS testing revealed a TRAF1::ALK translocation, which led to a revised diagnosis of stage IV ALK-positive anaplastic large cell lymphoma (ALCL), a curable cancer. The patient then started treatment with brentuximab vedotin, cyclophosphamide, doxorubicin, etoposide, and prednisone followed by autologous stem cell transplantation consolidation, given the very extensive disease at presentation. She remains in continued complete remission at 28 months. In this case, NGS was essential in establishing the correct diagnosis and selection of therapy in high-risk ALCL. NGS testing should be a routine component of the oncology patient workup to complement standard diagnostic modalities.